Recommending Relevant Services in Electronic and Mobile Health Platforms - Noveski, Gjorgji; Valič, Jakob (Informatica, 2022)
Electronic and mobile health (EMH) is becoming an integrated part of healthcare as we move in the future. The opportunity in bringing closer healthcare services with the advent of the internet is growing larger. This is why it is important to adequately provide those services to the people that need them and to also further improve them. Regarding electronic and mobile healthcare systems, it is fairly easy for users to get lost while searching for some information due to the vast amount of data that is present for different illnesses, healthcare institutions and healthcare services. In this paper we present a platform that provides various healthcare services to people, namely the Insieme platform (ISE-EMH). Knowing the difficulty of finding relevant information on platforms and that user preferences vary to a great extent, we additionally give an overview of an implementation of the recommendation system that is part of the Insieme platform which helps users pick services that might be relevant to them.